2022
DOI: 10.1038/s41522-022-00299-8
|View full text |Cite
|
Sign up to set email alerts
|

The car tank lid bacteriome: a reservoir of bacteria with potential in bioremediation of fuel

Abstract: Bioprospecting of microorganisms suitable for bioremediation of fuel or oil spills is often carried out in contaminated environments such as gas stations or polluted coastal areas. Using next-generation sequencing (NGS) we analyzed the microbiota thriving below the lids of the fuel deposits of diesel and gasoline cars. The microbiome colonizing the tank lids differed from the diversity found in other hydrocarbon-polluted environments, with Proteobacteria being the dominant phylum and without clear differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
2
3
0
Order By: Relevance
“…Our analysis of the taxonomic core microbiome-the bacterial taxa that frequently colonize host plants across broad ecological contexts (Neu et al, 2021;Risely, 2020)-showed that neopolyploidy broadened the core microbiome of S. polyrhiza (Table 4). Following previous studies that have used a 50% frequency cut-off in determining the core versus non-core microbiome taxa (Ainsworth et al, 2015;Vidal-Verdu et al, 2022), we found that neopolyploid core microbiome comprised an additional 15 taxa on top of the 55 taxa they share with the diploid core microbiome (Table 4). This result reveals that neopolyploidy in S. polyrhiza causes a broader biotic niche by associating with 27% more bacterial taxa.…”
Section: Polyploidy Broadens the Core Microbiomesupporting
confidence: 54%
See 1 more Smart Citation
“…Our analysis of the taxonomic core microbiome-the bacterial taxa that frequently colonize host plants across broad ecological contexts (Neu et al, 2021;Risely, 2020)-showed that neopolyploidy broadened the core microbiome of S. polyrhiza (Table 4). Following previous studies that have used a 50% frequency cut-off in determining the core versus non-core microbiome taxa (Ainsworth et al, 2015;Vidal-Verdu et al, 2022), we found that neopolyploid core microbiome comprised an additional 15 taxa on top of the 55 taxa they share with the diploid core microbiome (Table 4). This result reveals that neopolyploidy in S. polyrhiza causes a broader biotic niche by associating with 27% more bacterial taxa.…”
Section: Polyploidy Broadens the Core Microbiomesupporting
confidence: 54%
“…We used a minimum 0.1% relative abundance as a cut‐off for being included in the core. After accounting for the relative abundance cut‐off, we followed other similar studies in their determination of the core bacterial microbiome by using a frequency cut‐off of 50% (Ainsworth et al, 2015; Vidal‐Verdu et al, 2022), meaning that any “core” ASV must be colonized in at least 50% of all samples within any one of the three possible ploidy groupings (2× exclusive, 2× and 4× combined and 4× exclusive core microbiome). However, we also report on a second, more conservative relative frequency cut‐off of ≥75% to evaluate how restricted the core microbiome estimation can be to relative frequencies within groups.…”
Section: Methodsmentioning
confidence: 99%
“…7). Following previous studies that have used a 50 % frequency cut-off in determining the core versus non-core microbiome taxa (Ainsworth et al, 2015;Vidal-Verdu, Gomez-Martinez, Latorre-Perez, Pereto, & Porcar, 2022), we found that neopolyploid core microbiome was comprised of an additional 15 taxa on top of the 55 taxa they share with the diploid core microbiome (Fig. 7).…”
Section: Discussionsupporting
confidence: 54%
“…Here, we describe the microbial profile of “things”, which, despite being in constant contact with humans or the human activity, do not necessarily share a microbiome characterized by human-associated microorganisms but, instead, represent microbial micro-niches with their own selective pressures and characteristic microbiomes. Here, we look briefly into the previous research on the natural microbiomes of “things”, and we use examples such as that of the photovoltaic panels [ 20 , 21 ], the car tank lid [ 22 ], or the microbiome of automobile air-conditioning systems [ 23 ]. The focus of the “Microbiome of Things” (MoT), the existence of which we propose here, is analogous to the “Internet of Things” (IoT) concept.…”
Section: Microbiomes On Artificial Devicesmentioning
confidence: 99%